2006
DOI: 10.1016/j.ijsolstr.2005.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of damage mechanism and validation of a fracture model based on mesoscale approach in spalling of titanium alloy

Abstract: The subject of this paper is identification of the physical mechanisms of spalling at low impact velocities for Ti-6Al-4V alloy and determination of the macroscopic stress of spalling via meso-macro approach. Spalling is a specific mode of fracture which depends on the loading history. The aspects of the initial microstructure and its evolution during plastic deformation are very important. In order to identify the spalling physical mechanisms in titanium alloy, numerous pictures by the optical microscopy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Microstructural analysis of recovered specimens by Tyler et al [78] showed that voids seemed to nucleate at the interface between the α and β phase. Boidin et al [79] also observed that voids nucleated at the interface between the α and β phase in Ti-6Al-4V with a lamella-based microstructure. The voids were observed to coalesce owing to highly localized plastic bridging between facets.…”
Section: (B) Spall Response Of Titaniummentioning
confidence: 93%
“…Microstructural analysis of recovered specimens by Tyler et al [78] showed that voids seemed to nucleate at the interface between the α and β phase. Boidin et al [79] also observed that voids nucleated at the interface between the α and β phase in Ti-6Al-4V with a lamella-based microstructure. The voids were observed to coalesce owing to highly localized plastic bridging between facets.…”
Section: (B) Spall Response Of Titaniummentioning
confidence: 93%
“…Steinberg, 1991;Meyers, 1994;Johnson et al, 1994;Kanel et al, 1997;Millett et al, 2002;Lopatnikov et al, 2004;and Zaretsky et al, 2005;Gebbeken et al, 2006;Gu and Ravichandran, 2006;Bronkhorst et al, 2006), and numerous phenomenological as well as microscopic models have been developed (e.g. Wallace, 1981;Steinberg et al, 1980;Swegle and Grady, 1985;Meyers, 1994;Kanel et al, 1995;Nellis et al, 2003;Bourne and Gray, 2003;Krü ger et al, 2003;and Chijioke et al, 2005;Boidin et al, 2006;Petit and Dequiedt, 2006). However, in spite of a perfectly adequate general understanding, experimental methodology, and theory, material models do not agree in detail, especially for anisotropic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that high microhardness of ASB in zirconium alloy was mainly due to grain refining [19]. However, other researchers considered that the higher hardness within ASB was because its microstructure was quenched by the surrounding material [52]. In the present experiments, the gradient structure of the shear region after large plastic deformation led to the difference in microhardness and a large number of fine equiaxed grains in the ASB caused the microhardness to increase.…”
Section: Resultsmentioning
confidence: 60%